South-South Regional Integration and Industrial Growth : The Case of the Andean Pact - Madani, Dorsati H. (World Bank, Washington, DC, 2014)
Has the revival of the Andean Pact affected the industrial growth of Bolivia, Colombia, and Ecuador? Has this regional agreement had greater effects tha unilateral liberalization? The author explores two potential channels for industrial growth: scale effects and variety of imported intermediate inputs. She analyzes data from 2 countries (classified at the three-digit level of ISIC) across three countries. The results show that: 10 The variety of intermediate inputs originating from nonregional partners has a significant positive impact on growth in a handful of industries. 2) The effect of regional variety is at best mixed. This lends preliminary support to the argument that unilateral liberalization will have a positive impact on output growth through the channel of imported intermediate inputs. There is significant homogeneity in industry-level returns to scale. Moreover, in the three Andean countries studied, cross-country scale effects were small and negative. Therefore, the three countries should not expect large or across-the-board gains through scale effects from their regional arrangement.